Sexual Abuse against Male Children and the Related National Practices and International Legal Obligation of Nepal - Sapkota, Smriti (Kathmandu School of Law Review, 2022)
Nepal has aimed to prevent and protect children from all forms of violence, abuse, and exploitation by adopting a broad range of national laws, rules, regulations, and policies along with the international legal commitments. However, these rights are frequently violated. Sexual abuse against male children and pedophilia are rising issues of child sexual abuse that have remained a hidden phenomenon over the years. This paper is thus an endeavor to study the sexual abuse against male children via the pedophilic character of offenders in the context of Nepal. By adopting key informant interview methods, assessing national and international legal practices, and collecting information from the secondary sources; this paper examines the relationship among child sexual abuse and pedophilia, the sociological aspects of male child sexual victimization, and the modus operandi to cause abuse. In addition, this research delves into analyzing Nepal’s existing legal commitments to address sexual abuse in the international arena and the legal challenges Nepal is explicitly facing in addressing male child sexual abuse via pedophilia. The paper assesses the roles of various stakeholders in standing together to vigorously address this issue.